Influence of directing management at primary and secondary school educational institutions (2014)
This article identifies and characterizes the different styles of directing management used at educational institutions (herein referred to as x and y). At each institution, the style of leadership and implications of its use within the processes of school life is examined, because its specific contexts facilitate a differentiated recognition. The article also analyzes diverse interactions that occur in the daily lives of institutions, showing a close connection between, on the one hand, directing styles, leadership, management and communication, and on the other hand, personality, ethical and professional training, style, formulas for treating those who are directed, and basic factors when directing the destinies of those under the institution’s charge. In this realm, the management of interests, conflicts, needs, expectations, attitudes, etc. among those who share and “coexist” within the institution produces a unique social and cultural construction that benefits and affects the training processes that take place.